Many-faced global suburbanization - L. A. Ovchintseva (RUDN journal of Sociology)
The article is a review of the book by A.S. Breslavsky Suburbanization and the Future of Russian Cities: An Introduction (Moscow: Center for Humanitarian Initiatives; 2024. 170 p.). The author briefly presents an overview and interesting examples of regional forms and various ways of suburbanization, since the book is an introduction to this subject field. The author focuses not on details (figures and illustrations) but on the systematization of knowledge and data - the book includes an extensive reference list, allowing all interested readers to continue studies of suburbanization.